Principales manifestaciones clínicas del síndrome nefrótico y su manejo terapéutico - Valarezo Reyes, Erick Alberto (Machala : Universidad Técnica de Machala, 2019)
The nephrotic syndrome is characterized by proteinuria> 3.5 grams, edema, hypoalbuminemia and dyslipidemia. Its incidence is 2-7 per 100,000 children worldwide. Produced by a defect in the podocytes and the glomerular filtration barrier, among other factors. The main complications are thromboembolism, infections and acute kidney injury. OBJECTIVE: To describe the pathophysiology of the main clinical manifestations in the nephrotic syndrome, and their therapeutic management MÉTHODS: Through a search through the databases such as the VIRTUAL HEALTH LIBRARY, MEDLINE, EMBASE, COCHRANE, GOOGLE SCHOLAR, HINARY and PUBMED CENTRAL, a review of titles of interest was subsequently made, and finally selection of studies, using the criteria of inclusion and exclusion, with a period of 11 years (2008-2019) DEVELOPMENT: Diet is important in the treatment of nephrotic syndrome, including low sodium, and even gluten-free, dairy-free, and consumption of omega-3 fatty acids and in countries such as China the consumption of Monascus purpureus serum. In the pharmacology of proteinuria, steroids, immunosuppressants, hormone therapy and even ACE inhibitors, in edema, the use of diuretics, and in dyslipidemia, the use of statins, among other hypolipidemic drugs under study, currently the apheresis of LDL and inhibitors. of PCSK9 CONCLUSION: The main manifestations of the nephrotic syndrome are proteinuria, edema, hypoalbuminemia and dyslipidemia, knowing their treatment is important to improve the quality of life of the patient and prevent recurrence.
El síndrome nefrótico se caracteriza por proteinuria > 3,5 gramos, edema, hipoalbuminemia y dislipidemia. Su incidencia es 2-7 por cada 100.000 niños en todo el mundo. Producido por un defecto en los podocitos y la barrera de filtración glomerular, entre otros factores. Las principales complicaciones son el tromboembolismo, las infecciones y la lesión renal aguda. OBJETIVO: Describir la fisiopatología de las principales manifestaciones clínicas en el síndrome nefrótico, y su manejo terapéutico MÉTODOS: Mediante una búsqueda a través de las bases de datos como la BIBLIOTECA VIRTUAL EN SALUD, MEDLINE, EMBASE, COCHRANE, GOOGLE SCHOLAR, HINARY y PUBMED CENTRAL, posteriormente se hizo una revisión de títulos de interés, y finalmente selección de estudios, mediante los criterios de inclusión y exclusión, con un período de 11 años (2008-2019) DESARROLLO: La dieta es importante en el tratamiento del síndrome nefrótico, entre ellas la hiposódica, e incluso sin gluten, sin lácteos, y el consumo de los ácidos grasos omega-3 y en países como china el consumo del suero de Monascus purpureus. En lo farmacológico en la proteinuria los esteroides, inmunosupresores, la terapia hormonal e incluso los IECA, en el edema el uso de diuréticos, y en la dislipidemia el uso de estatinas, entre otras hipolipemiantes en estudio, actualmente la aféresis de LDL y LOS inhibidores de PCSK9 CONCLUSIONES: Las principales manifestaciones del síndrome nefrótico son la proteinuria, edema, hipoalbuminemia y dislipidemia, conocer su tratamiento es importante para mejorar la calidad de vida del paciente y evitar recidivas.
Keywords: PROTEINURIA; EDEMA; HIPOALBUMINEMIA; DISLIPIDEMIA